2016
DOI: 10.1111/asj.12691
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Lactobacillus plantarum and Bacillus subtilis on rumen fermentation and the bacterial community in calves

Abstract: The objective of this study was to assess the effect of dietary probiotics on rumen fermentation and the bacterial community in dairy calves. Twelve Holstein calves were randomly allocated to three treatments: a basal diet, the basal diet supplemented with Lactobacillus plantarum GF103 (LB) or basal diet supplemented with a mixture of Lactobacillus plantarum GF103 and Bacillus subtilis B27 (LBS). A milk replacer was fed to calves from 8 days of age. A starter and alfalfa hay was offered ad libitum from 21 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 27 publications
(64 reference statements)
3
18
0
1
Order By: Relevance
“…Importantly, it should be noted that FSBM was prepared by incubation of SBM with Bacillus subtilis, which has been shown to have probiotic effects. Hence, Bacillus subtilis may enter the rumen and alter the microbial composition, fermentation and digestive processes of the rumen 33,34 . For example, Zhang et al 33 found that the probiotic bacteria (a mixture of Lactobacillus plantarum and Bacillus subtilis) influenced the rumen bacterial community and reduced the numbers of cellulolytic bacteria such as Ruminococcus albus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, it should be noted that FSBM was prepared by incubation of SBM with Bacillus subtilis, which has been shown to have probiotic effects. Hence, Bacillus subtilis may enter the rumen and alter the microbial composition, fermentation and digestive processes of the rumen 33,34 . For example, Zhang et al 33 found that the probiotic bacteria (a mixture of Lactobacillus plantarum and Bacillus subtilis) influenced the rumen bacterial community and reduced the numbers of cellulolytic bacteria such as Ruminococcus albus.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, Bacillus subtilis may enter the rumen and alter the microbial composition, fermentation and digestive processes of the rumen 33,34 . For example, Zhang et al 33 found that the probiotic bacteria (a mixture of Lactobacillus plantarum and Bacillus subtilis) influenced the rumen bacterial community and reduced the numbers of cellulolytic bacteria such as Ruminococcus albus. Therefore, further research with killed colonies (i.e., sterilized FSBM) is required to distinguish the role of peptide size and Bacillus subtilis (as a probiotic bacterium) in rumen physiology.…”
Section: Discussionmentioning
confidence: 99%
“…The VFA concentration and molar proportion of each VFA at 12 and 24 h of fermentation were measured according to Zhang et al (2016). Briefly, 1 ml of the rumen fluid filtrate was mixed with 25% metaphosphoric acid solution, which contained 2% 2‐ethyl butyrate, and then frozen at –20°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The developing rumen of the dairy calf provides a potential opportune period to direct microbial establishment (Yáñez-Ruiz et al, 2015). Early dietary interventions, probiotics, and adult rumen contents have been used in an attempt to modify the rumen and fecal microbial communities of young ruminants (Schönhusen et al, 2003; Ishaq et al, 2015; Fouladgar et al, 2016; Zhang et al, 2017). Rumen contents inoculated into calves have included the use of mixed ruminal microbiota from either whole rumen fluid or a ruminal bolus.…”
Section: Introductionmentioning
confidence: 99%